Examen especial al sistema integrado de desarrollo de talento humano del gobierno autónomo descentralizado municipal de Lago Agrio, provincia de Sucumbíos del periodo enero a diciembre de 2014 - Gaviria Vallejo, Judy Paola (2016)
The thesis is called "SPECIAL CONSIDERATION TO THE INTEGRATED DEVELOPMENT OF HUMAN TALENT GOVERNMENT decentralized autonomous MUNICIPAL Lago Agrio, Sucumbios province PERIOD JANUARY TO DECEMBER 2014" was developed for the purpose of determining compliance with the laws, regulations and standards governing the Integrated Human Resource System, which comprises five subsystems for efficient management of human resources in the Municipal Government of Lago Agrio and execute the three phases of the special examination, to issue the corresponding final report comments, conclusions and recommendations. In the special examination it proceeded to analyze five human talent subsystems are planning human talent; classification; Recruitment and selection of personnel; education and training; and performance evaluation in order to determine the degree of risk of internal control and trust that provide these for the administration of human resources in the Municipal Government of Lago Agrio. It can be concluded that the management of the Integrated Human Resource Development is poor, lack of proper implementation of the annual planning of human talent; no manual job classification; breach of the percentage of staff with disabilities; trainings that do not appear in the annual planning; and performance evaluations without parameters and goals. With this contribution the Decentralized Autonomous Municipal Government of Lago Agrio to improve Human Resource Management.